(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The existence of differences and confusion in the approaches to learning English crucially pose challenges to investigate the approaches that may either enrich or hinder how English language learners go about learning. This study investigated the approaches to learning English adopted by EFL undergraduate students. In addition, it examined if there is a difference between the approaches to learning adopted by students in different departments at the Faculty of Education, Sirte University in Libya. Data were collected quantitatively from 70 students using the Biggs’ Study Process Questionnaire (SPQ) as a diagnostic instrument for assessing students’ perceived approaches to learning. The results indicated that most students adopted surface approaches. These approaches to learning gained the highest mean score (M= 4.55) whereas deep approaches were the low ( M =1.77). The results also explained differences among students’ approaches to learning English in different departments. The key findings provide inputs to the academic institutions on the learning process and act as a reference for decision-making and improvement in the learning approaches of students. suggestions for teachers, educational policymakers and future research have been provided in detail in this study.